Autologous CIK cells combined with chemotherapy as the first-line treatment for locally advanced or metastatic gastric cancer is safe and feasible - Ma, Xiaoting; Peng, Liming; Wang, Junqing; Gao, Lizhen; Zhang, Wen; Lu, Xu; Liu, Jingwei; Yang, Lin (Frontiers in Immunology, 2023)
Aim To evaluate the safety and initial efficacy of autologous cytokine-induced killer (CIK) cells combined with S-1+oxaliplatin (SOX) as the first-line treatment for locally advanced or metastatic gastric cancer (GC).In this two-arm, single-center exploratory trial, patients with locally advanced or metastatic GC were randomly assigned (1:1) to receive autologous CIK cells in combination with SOX (CIK-SOX) or SOX alone. The primary endpoint was the incidence of adverse events (AEs). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR) served as the secondary endpoints.Fifty-nine patients were enrolled in the study between November 20, 2014 and September 6, 2017. A total of 31 patients received CIK-SOX and 28 patients received SOX. The most common AEs in both groups were gastrointestinal reaction, leucopenia, neutropenia, anemia, thrombocytopenia, hyperbilirubinemia, and elevated aspartate transaminase concentration, with a higher incidence of these conditions in the SOX group. The median PFS for the CIK-SOX and SOX groups was 6.9 and 4.9 months, respectively (hazard ratio (HR) 0.80, p=0.45). The respective median OS values were 17.8 and 9.75 months (HR 0.76, p=0.34). Patients who received more than three injections of specific lymphocyte subsets benefited the most from this combination therapy. Cox univariate and multivariate analyses showed that tumor metastasis to more than two organs was the main risk factor for PFS and OS. A total of 29 patients in the CIK-SOX group and 25 in the SOX group had measurable lesions. The ORR for the CIK-SOX and SOX groups was 55.2% and 32.0%, while the DCR was 93.1% and 88.0%, respectively.The safety of CIK-SOX as the first-line treatment for patients with locally advanced or metastatic GC was good. Although the PFS and OS in the CIK-SOX group were not statistically significantly different compared to the values in the SOX alone group, this treatment increased the PFS and OS duration, with the absolute improvement in OS of about 8.05 months.Continuous benefit from the CIK-SOX treatment was observed during long-term follow-up.